The Impact of Organizational Change and Work Autonomy on Employee Well-Being - Janet Omega; Elfrida Viesta Napitupulu (Journal Research of Social Science, Economics, and Management, 2025)
This study aims to analyze and empirically examine the impact of Organizational Change and Job Autonomy on Employee Well-Being. The background of this research is based on the importance of maintaining employee well-being amidst structural changes and autonomy demands in modern work environments. This research employs a quantitative approach with a sample of 36 employee respondents. Data were analyzed using multiple linear regression techniques. The results show that Organizational Change and Job Autonomy simultaneously have a significant and positive effect on Employee Well-Being. This finding is supported by a coefficient of determination (R²) value of 0.721, indicating that 72.1% of the variation in Employee Well-Being can be explained by the two independent variables. The results conclude that effective management of organizational change and the provision of adequate job autonomy are key factors in enhancing employee well-being.